SmartHolder: sensing and raising families' awareness of tooth brushing habits - Caraban, Ana; Ferreira, Maria José; Belim, Vítor; Lyra, Olga; Karapanos, Evangelos (My University, 2014)
With an increasing emphasis on behavior change technologies, interest has grown over time also on the role of HCI in motivating healthy tooth brushing habits on children. In this paper we present the design and development of SmartHolder, a toothbrush holder that senses the frequency and duration of toothbrush practices and motivates healthy tooth brushing habits, through raising family members' awareness of each other's practices. Wed first present two preliminary studies about children's and adults' tooth brushing behaviors and how these are influenced by social interactions within the family. We conclude through a presentation of early conceptual designs as well as an initial working prototype of SmartHolder. Copyright 2014 ACM.
Keywords: Persuasive technology; Children; Tooth brushing